G46(P) Maintenance enteral nutrition post induction therapy in paediatric crohns disease. (27th April 2016) - Gavin, J; Ashton, JJ; Heather, N; Marino, LV; Beattie, RM
Abstract : Introduction: Several studies suggest that maintenance enteral nutrition (MEN) post induction in Crohns Disease (CD) may have a role in prolonging remission. This retrospective study compares growth outcomes and relapse rate in CD patients supplemented with MEN versus an unsupplemented group. Methods: Data including anthropometry, treatment type and outcome were collected for 78 patients at diagnosis, start of MEN, at 3 months and at 1 year from 2012–14. Patients who received MEN (n = 42) post induction therapy were compared with those on normal diet (ND; n = 36). Clinical remission was determined using a physician global assessment and blood biochemistry. Relapse was defined as a change in medication due to symptoms. Data are presented as median values. Results: Age at diagnosis was 13 years, 62/78 (79%) were male. All groups had similar rates of clinical remission post induction therapy. The length of MEN was 3 months. The energy content of MEN was 635kcals representing 33% of energy requirement. 32/42 (76%) MEN patients received EEN as induction therapy, 7/42 (17%) received PEN and 3/42 (7%) steroids. 24% of MEN group relapsed within 6 months of diagnosis versus 53% ND (p = 0.009). Body mass index z score (BMIZ) significantly improved in both groups (MEN: p < 0.001; ND: p = 0.02). There were no differences in height-for-age z scores (HAZ). Conclusion: CD patients treated with MEN who received EEN or PEN as induction therapy were less likely to relapse within 6 months of diagnosis. BMIZ improved towards normal in both groups. Prolonged nutritional support from diagnosis may extend length of remission.